Mycorrhizal Fungi Utilization in Agriculture and Forestry - Radhakrishnan, Ramalingam (IntechOpen, 2021)
Microbes are essential components of the ecosystem. Mycorrhizal fungi in the rhizosphere support or inhibit plant growth naturally. Plant growth-promoting fungi help to improve crop yield and crop sustainability in adverse environmental conditions including soil salinity, drought, high and low temperatures, and infections from pathogens and pests. Mycorrhizal fungi secrete plant growth-promoting substances, enzymes, and other metabolites, all of which play a vital role in enhancing the productivity of economically important plants. These fungi also reduce the need to use chemicals in agriculture, which helps to minimize soil pollutants. This book provides updated information on the production and utilization of mycorrhizal fungi for sustainable agriculture and forestry.